Economic culture of the Republic of Belarus population: normative model and current state - Haurylik, Aksana N. (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
It is noted that a sociological assessment of the effectiveness of ongoing reforms requires understanding the extent to which the current economic culture of the population corresponds to the economic development model and state policy priorities. The economic culture of residents of the Republic of Belarus is examined, and the normatively established and desirable characteristics of the population’s economic culture are compared with its current characteristics at the current stage of social development. Scientific literature, regulatory documents, empirical sociological research data, and statistical data are analysed. Conclusions are drawn regarding the degree to which the current state of the economic culture of residents of the Republic of Belarus corresponds to normative concepts.
Keywords: normative ideas; socio-economic development; financial literacy; economic culture